Diabetic retinopathy and diabetic kidney disease, either isolated or associated, impact on the 10-year risk of cardiovascular disease: are we dealing with similar conditions? - Clara Krummenauer Maraschin; Janine Alessi; Mateus Augusto dos Reis; Gabriela Oliveira Gonçalves Molino; Gabriela Heiden Teló; Beatriz D. Schaan (Archives of Endocrinology and Metabolism)
Abstract Objective: To evaluate the association between diabetic retinopathy, diabetic kidney disease, and the 10-year risk of atherosclerotic cardiovascular disease in patients with diabetes. Subjects and methods: A cross-sectional study was performed involving patients diagnosed with either type 1 or type 2 diabetes mellitus. Participants were classified into four groups: DM (patients without diabetes-related complications), DR (patients with diabetic retinopathy only), DKD (patients with diabetic kidney disease only), and DR + DKD (patients with both diabetic retinopathy and diabetic kidney disease). The primary outcome was the 10-year risk assessment for cardiovascular events, calculated using the American Heart Association’s atherosclerotic cardiovascular disease score. Results: A total of 571 patients were selected including 128 with type 1 diabetes (average age of 39.4 ± 15.1 years; 48.4% female) and 443 with type 2 diabetes (average age of 59.5 ± 11.9 years; 66.4% female). Among the participants with type 2 diabetes, the cardiovascular risk was 15.2 ± 14.6% for the DM group, 15.7 ± 10.7% for the DR group, 22.5 ± 16.7% for the DKD group, and 21.5 ± 15.1% for the DR + DKD group, reflecting a significantly higher cardiovascular risk in the groups with renal involvement (P <0.001). For those with type 1 diabetes, the DM group had a risk of 6.1 ± 8.9%, the DR group 8.9 ±11.8%, the DKD group 5.4 ± 8.8%, and the DR + DKD group 6.1 ± 9.5%. The mean difference in risk between the groups was not statistically significant. Conclusion: In patients with type 2 diabetes, those with diabetic kidney disease appeared to have a higher theoretical risk of cardiovascular disease compared to those with only diabetic retinopathy.